Assessment of the physicochemical properties of the sediment from the Gangetic floodplain wetlands of West Bengal, India, with GIS and a statistical approach - Das, Basanta Kumar; Saha, Ajoy; Das, Archan Kanti; Chandra, Purna; Mondal, Kausik; Kayal, Tania; Chakraborty, Sangeeta; Bhattacharya, Shreya; Sahoo, Bigan Kumar; Jana, Chayna (Frontiers in Environmental Science, 2024)
Bottom sediments play a pivotal role in wetland productivity, and here eight Gangetic floodplain wetlands of India were studied to assess the sediment physicochemical characteristics and textural analysis. During the period of study of one year, the pH (6.90 to 8.04), EC (0.20 to 1.64 mS/cm), CaCO3 (1.75 to 14.50%), available nitrogen (10.22 to 22.23 mg/100g sediment) and total nitrogen (80.4 to 333.8 mg/100g sediment), available phosphorus (0.20 to 5.61 mg/100g sediment) and total phosphorus (19.63 to 173.33 mg/100g sediment) were recorded. The sediment quality parameters differ significantly (p > 0.05) among the wetlands. While seasonal variation was only observed on total nitrogen and total phosphorus contents. Sediments were dominated by sand. Sediment nutrient (C, N and P) stoichiometry of wetlands depicted comparatively little higher C/P (5.96 to 66.32) ratio and lower C/N (3.34 to 22.76) and N/P (1.12 to 9.25) ratios revealed that the physicochemical characteristics of the sediments are influenced by anthropogenic sources. Principal component analysis showed the influence of both natural and anthropogenic causes on wetland ecosystems. The geographic information system (GIS) interpolation approach was used in combination with laboratory analysis methods to give a complete spatial resolution of the sediment quality of each wetland. The study suggests that these wetlands' sediment quality is favourable for fish culture but requires proper management practices to achieve sustainable production. As it is the first time where monitoring physicochemical properties of sediments of these wetlands are presented, this study can be used as a baseline data for comparison in future environmental assessment of the wetlands.